Multi-objective optimization of flexible positioning platform considering displacement frequency and dynamic stiffness responses - Lufan Zhang; Heng Yan; Hehe Sun; Mengyuan Hu (Scientific Reports)
Abstract In order to study the impact of periodic loads on the vibration performance of the flexible positioning platform in the key mechanisms of the ultra-high acceleration macro–micro motion platform, and to improve the performance and stability of the platform, this paper combined SolidWorks and ANSYS Workbench to conduct modal analysis and harmonic response of the flexible positioning platform. Analysis to obtain its inherent characteristics. The piezoelectric actuator provides the driving force of the micro-motion platform and achieves precise micro-motion displacement positioning, which is used to study the frequency response results of simple harmonic excitation. By analyzing the node displacement frequency response, the dynamic stiffness response characteristics of the hinge and micro-motion platform of the flexible positioning platform under actual loads were determined, and potential dangerous areas were identified. Finally, both response surface optimization and direct optimization methods were used to optimize the design of the hazard zones for the flexible positioning platform, and the results of both optimization models were validated. The findings indicate that the direct optimization results validate the accuracy of the response surface optimization. After response surface optimization, the first-order natural frequency of the flexible positioning platform increased by 3.28%, and the mass decreased by 1.84%. The maximum deformation and response peak of the first-order vibration mode decrease, and the dynamic stiffness increases. This research provides valuable reference for the structural design and vibration performance optimization of positioning platforms containing flexible hinges.